Phosphorylation of CRY1 Serine 71 Alters Voluntary Activity but Not Circadian Rhythms In Vivo. Issue 4 (August 2019) - Vaughan, Megan; Jordan, Sabine D.; Duglan, Drew; Chan, Alanna B.; Afetian, Megan; Lamia, Katja A.
Circadian clocks allow organisms to anticipate repetitive changes in their environment such as food availability, temperature, and predation. While they most clearly manifest at the behavioral level, driving sleep-wake cycles, for example, they also provide critical temporal regulation at the level of individual tissues. Circadian clocks within organs act to ensure that each tissue is functioning in a coordinated manner to anticipate the needs of the organism as a whole but also allow for adaptation of organs to their local environment. One critical aspect of this environment is energy availability, which is communicated at the cellular level via changes in metabolites such as ATP, calcium, and NADH. AMP-activated protein kinase (AMPK) is both sensitive to fluctuations in secondary metabolites and capable of resetting the circadian clock via destabilization of the core clock components CRY and PER. Phosphorylation of serine 71 of CRY1 by AMPK destabilizes CRY1 by decreasing its interaction with binding partner PER2, thus enabling greater association with the SCF complex substrate adaptor FBXL3. Here, we describe a transgenic mouse harboring germline mutation of CRY1 serine 71 to alanine. Unexpectedly, this mutation does not affect the steady-state level of CRY1 protein in mouse livers or quadriceps. We also did not detect changes in either behavioral or molecular circadian rhythms, but female Cry1 S71A mice exhibit decreased voluntary locomotor activity compared with wild-type littermates. Together, these findings suggest that phosphorylation of CRY1 serine 71 is not required for the regulation of circadian rhythms under normal physiological conditions. However, it may be involved in responding to metabolic challenges or in other aspects of physiology that contribute to voluntary activity levels.